2011
DOI: 10.1182/blood-2011-06-361881
|View full text |Cite
|
Sign up to set email alerts
|

B-cell replication history and somatic hypermutation status identify distinct pathophysiologic backgrounds in common variable immunodeficiency

Abstract: Common variable immunodeficiency disorder (CVID) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 49 publications
7
110
1
Order By: Relevance
“…In line with the clinical differences, analysis of the earlier presented B-cell patterns 9 revealed that defective B-cell production and early peripheral B-cell maturation or survival defect (B-cell patterns 1 and 2, respectively) were seen exclusively in CVID. In addition, we showed that these two B-cell patterns are associated with non-infectious disease-related clinical complications.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In line with the clinical differences, analysis of the earlier presented B-cell patterns 9 revealed that defective B-cell production and early peripheral B-cell maturation or survival defect (B-cell patterns 1 and 2, respectively) were seen exclusively in CVID. In addition, we showed that these two B-cell patterns are associated with non-infectious disease-related clinical complications.…”
Section: Discussionmentioning
confidence: 83%
“…9 The patterns are based on the composition of the peripheral B-cell compartment and the replication history and somatic hypermutation frequency of the individual Bcell subsets and are indicative for the pathophysiological background of the antibody deficiency. 9 The B-cell patterns can be easily determined by flow cytometry. Our earlier detailed molecular assays on sorted peripheral Bcell subsets were used to characterize the patterns, but are not used to define the pattern in individual patients.…”
Section: Peripheral B-cell Subset Patterns Are Different In Cvid and Iphmentioning
confidence: 99%
See 2 more Smart Citations
“…As mutations in genes encoding T and B cell activation molecules and receptors, such as inducible T cell costimulator (ICOS), transmembrane activator and calcium modulator and cyclophilin ligand interactor (TACI), B cell activating factor-receptor (BAFF-R), B cell receptor complex (CD19, CD81, CD21), and CD20 have been detected in less than 10% of patients affected by CVID (30), the identification of genetic defects is limited by disease immunologic heterogeneity. A classification of CVID dependent of immune parameters of the B cell compartment with analysis of replication history and somatic hypermutation status has been proposed by Driessen et al (31). The pathophysiologic B cell pattern associated with peripheral maturation or survival defects was associated with a normal transitional B cell number and a reduction of naive mature and memory B cells in CVID patients and also in the hypogammaglobulinemic children studied.…”
Section: Discussionmentioning
confidence: 99%